The price of neonatal intensive care outcomes – in-hospital costs of morbidities related to preterm birth - Rolnitsky, Asaph; Unger, Sharon; Urbach, David; Bell, Chaim M. (Frontiers in Pediatrics, 2023)
Background Neonatal care for preterm babies is prolonged and expensive. Our aim was to analyze and report costs associated with common preterm diagnoses during NICU stay. Methods We analyzed data from the Ontario healthcare data service. Diagnoses were collated by discharge ICD codes, and categorized by gestational age. We calculated typical non parametric statistics, and for each diagnosis we calculated median shifts and generalized linear mode. Results We included data on 12,660 infants between 23 and 30 weeks gestation in 2005-2017. Calculated cost increment with diagnosis were: Intestinal obstruction: $94,738.08 (95%CI: $70,093.3, $117,294.2), Ventriculoperitoneal shunt: $86,456.60 (95%CI: $60,773.7, $111,552.2), Chronic Lung Disease $77,497.70 (95%CI: $74,937.2, $80,012.8), Intestinal perforation $57,997.15 (95%CI:$45,324.7, $70,652.6), Retinopathy of Prematurity: $55,761.80 (95%CI: $53,916.2, $57,620.1), Patent Ductus Arteriosus $53,453.70 (95%CI: $51,206.9, $55692.7, Post-haemorrhagic ventriculomegaly $41,822.50 (95%CI: $34,590.4, $48,872.4), Necrotizing Enterocolitis $39,785 (95%CI: $35,728.9, $43,879), Meningitis $38,871.85 (95%CI: $25,272.7, $52,224.4), Late onset sepsis $32,954.20 (95%CI: $30,403.7, 35.515), Feeding difficulties $24,820.90 (95%CI: $22,553.3, $27,064.7), Pneumonia $23,781.70 (95%CI: $18,623.8, $28,881.6), Grade >2 Intraventricular Haemorrhage $14,777.38 (95%CI: $9,821.7, $20,085.2). Adjusted generalized linear model of diagnoses as coefficients for cost confirmed significance and robustness of the model. Conclusion Cost of care for preterm infant is expensive, and significantly increases with prematurity complication. Interventions to reduce those complications may enable resource allocation and better understanding of the needs of the neonatal health services.